2016
DOI: 10.1111/ijag.12243
|View full text |Cite
|
Sign up to set email alerts
|

Time of Formation of the First Supercritical Nucleus, Time‐lag, and the Steady‐State Nucleation Rate

Abstract: General equations are derived for the description of correlations between average time of formation of the first supercritical nucleus, time‐lag in nucleation, and steady‐state nucleation rate. In their implementation, a set of representative equations is employed modeling the time‐dependence of the nucleation rate as proposed first by Zeldovich and advanced by a variety of other authors. The analysis is performed for both isothermal–isobaric and time‐dependent process conditions. It is shown that, in general,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 44 publications
(140 reference statements)
0
42
0
Order By: Relevance
“…In a similar analysis, instead of , Angell et al [ 130 ] identified the characteristic time of crystallization with the time-lag in nucleation, . As already demonstrated in [ 64 , 129 ], this estimate is, in the range of temperatures Kauzmann was interested in, a much better approximation for the average time of formation of the first supercritical nucleus as compared to . The time-lag can be determined via Equation ( 16 ) [ 24 , 64 , 129 ]: …”
Section: Is the Kauzmann Paradox Really In Conflict With Basic Lawmentioning
confidence: 72%
See 2 more Smart Citations
“…In a similar analysis, instead of , Angell et al [ 130 ] identified the characteristic time of crystallization with the time-lag in nucleation, . As already demonstrated in [ 64 , 129 ], this estimate is, in the range of temperatures Kauzmann was interested in, a much better approximation for the average time of formation of the first supercritical nucleus as compared to . The time-lag can be determined via Equation ( 16 ) [ 24 , 64 , 129 ]: …”
Section: Is the Kauzmann Paradox Really In Conflict With Basic Lawmentioning
confidence: 72%
“…As already demonstrated in [ 64 , 129 ], this estimate is, in the range of temperatures Kauzmann was interested in, a much better approximation for the average time of formation of the first supercritical nucleus as compared to . The time-lag can be determined via Equation ( 16 ) [ 24 , 64 , 129 ]: …”
Section: Is the Kauzmann Paradox Really In Conflict With Basic Lawmentioning
confidence: 72%
See 1 more Smart Citation
“…The transition from no bubbles to bubbles occurs at Wnormaln2.3×1018 J. In the absence of established experimental constraints on the nucleation time lag or the induction time (Schmelzer et al, ) we neglect both. Under this assumption bubbles nucleate in an experimental sample when ( J max V ) −1 is less than the time over which the sample was held at its final pressure.…”
Section: Resultsmentioning
confidence: 99%
“…The quantity defines the time interval over which the first bubbles nucleate. This is also referred to as the "mean-lifetime of the metastable fluid" [41,42], the "average time of formation of the first supercritical nucleus" [43] or the "experiment/observation time" at the steady state [44]. The attainable length of this quantity is known to decrease as metastability increases, making the measurement of thermodynamic properties deep in the metastable region difficult or even practically impossible [28,36].…”
Section: Nucleation Ratesmentioning
confidence: 99%